D-mannose isomerase produced from Saccharothrix sp. CMU-k747 and some properties of the crude enzyme - Apiradee Siangsuepchart (2018)
The extracellular mannanase can catalyze the random hydrolysis of the mannan backbone and various polysaccharides consisting mainly of mannose. D-Mannose isomerase (d-MI) is an intracellular enzyme known to catalyze the reversible isomerization of D-mannose and D-fructose. Four hundred and forty five actinomycete strains were screened for mannanase production. In this study, thirty six strains produced mannanase activity and from those d-MI activity was detected in 15 isolates. The results also showed that cell extracts of CMU-K747 isolated from Phatup Cave in Nan province of Thailand, conferred the maximum yield of d-MI activity (0.301 ± 0.006 unit/ml) and mannanase activity (9.141 ± 0.285 unit/ml). Moreover, the optimum pH and temperature for crude d-MI were 8.0 and 40°C, respectively and the enzyme was stable at pH 4.0 to 11.0 (more than 85% of activity was retained). The enzyme from this strain showed thermostability and maintained more than 70% activity when incubated at 40°C for 1 h. The enzyme can catalyze the isomerization of D-mannose and D-lyxose, the specific activity was highest for D-mannose, followed by D-lyxose. Moreover, the equilibrium ratio between D-mannose and D-fructose was 50:50. The morphological and chemotaxonomy data supports that the strain CMU-K747 is non-Streptomyces. In addition, molecular analysis of 16S rDNA sequencing showed that CMU-K747 isolate was highly homologous to genus Saccharothrix with 99% identity. This is the first report of d-MI production by genus Saccharothrix from cave soil. This is the first report on this genus is capable of producing both mannanase and d-MI.